Reading activity prevents long-term decline in cognitive function in older people: evidence from a 14-year longitudinal study - Chang, Yu-Hung; Wu, I-Chien; Hsiung, Chao A. (International psychogeriatrics, 2021)
ABSTRACTObjectiveThis study examined the effect of daily life reading activity on the risk of cognitive decline and whether the effect differs regarding education levels. DesignA longitudinal study with 6-, 10-, and 14-year follow-up. SettingFace-to-face interviews with structured questionnaires at home. ParticipantsA representative sample of 1,962 Taiwanese community-dwelling older persons aged 64 and above, followed up in four waves of surveys over 14 years. MeasurementsBaseline reading frequencies were measured based on a scale of leisure activity. The Short Portable Mental Status Questionnaire was used to measure cognitive performance. We performed logistic regression to assess associations between baseline reading and later cognitive decline. Interaction terms between reading and education were to compare the reading effects on cognitive decline at different education levels. ResultsAfter adjusting for covariates, those with higher reading frequencies (≥1 time a week) were less likely to have cognitive decline at 6-year (adjusted odds ratio [AOR]: 0.54; 95% confidence interval [CI]: 0.34–0.86), 10-year (AOR: 0.58, 95% CI: 0.37–0.92), and 14-year (AOR: 0.54, 95% CI: 0.34–0.86); in a 14-year follow-up, a reduced risk of cognitive decline was observed among older people with higher reading frequencies versus lower ones at all educational levels. ConclusionsReading was protective of cognitive function in later life. Frequent reading activities were associated with a reduced risk of cognitive decline for older adults at all levels of education in the long term.